mtDNA-STING Axis Mediates Microglial Polarization via IRF3/NF-κB Signaling After Ischemic Stroke - Kong, Lingqi; Li, Wenyu; Chang, E; Wang, Wuxuan; Shen, Nan; Xu, Xiang; Wang, Xinyue; Zhang, Yan; Sun, Wen; Hu, Wei; Xu, Pengfei; Liu, Xinfeng (Frontiers in Immunology, 2022)
Neuroinflammation is initiated in response to ischemic stroke, and is usually characterized by microglial activation and polarization. Stimulator of interferon genes (STING) has been shown to play a critical role in anti-tumor immunity and inflammatory diseases. Nevertheless, the effect and underlying mechanisms of STING on microglial polarization after ischemic stroke remain unclarified. In this study, acute ischemic stroke was simulated using a model of middle cerebral artery occlusion (MCAO) at adult male C57BL/6 mice in vivo and the BV2 microglia oxygen-glucose deprivation/reperfusion (OGD/R) model in vitro. The specific STING inhibitor C-176 was administered intraperitoneally at 30min after MCAO. We found that the expression of microglial STING was increased following MCAO and OGD/R. Pharmacologic inhibition of STING with C-176 reduced the ischemia/reperfusion (I/R)-induced brain infarction, edema and neuronal injury. Moreover, blockade of STING improved neurological performance and cognitive function and attenuated neuronal degeneration in the hippocampus after MCAO. Mechanistically, both in vivo and in vitro, we delineated that STING could promote the polarization of microglia towards the M1 phenotype and restrain M2 microglia polarization via downstream pathways, including interferon regulatory factor 3 (IRF3) and nuclear factor-κB (NF-κB). In addition, mitochondrial DNA (mtDNA), which is released to microglial cytoplasm induced by I/R injury, could facilitate microglia towards M1 modality through STING signaling pathway. Treatment with C-176 abolished the detrimental effects of mtDNA on stroke outcomes. Taken together, these findings suggest that STING, activated by mtDNA, could polarize microglia to the M1 phenotype following MCAO. Inhibition of STING may serve as a potential therapeutic strategy to mitigate neuroinflammation after ischemic stroke.